2007
DOI: 10.1007/s00221-007-0879-2
|View full text |Cite
|
Sign up to set email alerts
|

Preserved dynamic cerebral autoregulation in the middle cerebral artery among persons with migraine

Abstract: Migraine affects the autonomous nervous system and a recent investigation has also proposed a severe disturbance of dynamic cerebral blood flow regulation in the middle cerebral artery during spontaneous blood pressure oscillations. This study investigates whether dynamic cerebral autoregulation is impaired in persons with migraine among a normal cohort. Out of 94 adults studied to establish normal values for dynamic autoregulation, 19 suffered from migraine according to IHS criteria (10 of them with aura). Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Meanwhile, no significant change was observed between patients with and without aura in MCA blood flow in response to vasodilator test which is an indication of a similarity in blood flow velocity in response to hypercapnia in these patients. This is similar to the studies reported by G. De Benedittis et al [33] and Reinhard et al 2007 [34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, no significant change was observed between patients with and without aura in MCA blood flow in response to vasodilator test which is an indication of a similarity in blood flow velocity in response to hypercapnia in these patients. This is similar to the studies reported by G. De Benedittis et al [33] and Reinhard et al 2007 [34].…”
Section: Discussionsupporting
confidence: 93%
“…All TCD parameters including PSV, DV, RI, and PI in both study and healthy control groups showed no statistical difference, this might indicate that there were either no change in cerebral blood flow at rest in patients with migraine versus control patients or the study group reading was not done in ictal period which was consistent with previously reported studies by Agnieszka et al and G. De Benedettis et al [32,33]. Furthermore, there was no statistical difference among migraine patients with aura versus without aura in relation to PSV, DV, RI, and PI, while similar blood flow velocity at rest in migraine patients with and without aura which was similar to previously reported studies by De Benedettis et al and Reinhard et al [33,34]. The relationship between cerebrovascular reactivity to hypercapnia that was induced by breath-holding, a strong significant increase was found in MCA blood flow in response to vasodilator test (hypercapnia) in study versus control groups (P value <0.0001), this may be due to changes at the level of the cerebral arterioles that affected the cerebral blood flow, and in turn led to changes in blood flow velocity as a response to hypercapnia (vasoreactivity) in migraineurs.…”
Section: Discussionsupporting
confidence: 91%
“…We could not confirm these results and found phase, gain, and Dx in the MCA to be unchanged between persons with and without migraine. 26 In that study, however, only 10 patients with MA were analyzed, and patients and controls were considerably older with a presumed lower disease activity.…”
Section: Previous Studies On Migraine and Autoregulationmentioning
confidence: 98%
“…Impairment of cerebral autoregulation (CA) is another possible mechanism that might render MA patients more vulnerable to cerebral ischemia. CA has been the subject of only a few studies in MA patients, with variable findings that may possibly be explained by differences in age of studied populations and in methods used to assess CA (68). In the present study, we compared CA in MA patients with healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%